The SDGs Perspective of TeleDoVIA Reliability for Cervical Cancer Elimination in 2030: A Cross Sectional Study in Indonesia - Widya Utami, Tofan; Nuranna, Laila; Purwoto, Gatot; Winarto, Hariyono; Fitriyadi Kusuma; Rizky Humairah , Inas; Faisha Rahma, Melly; Kekalih, Aria; Peters, Alexander AW (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: To describe the prevalence of HPV infection in women with negative Visual Inspection with Acetic Acid (VIA) and introduce Teleconsultation of Documented VIA (TeleDoVIA) as an objective test and provide a rationalization for recommending TeleDoVIA as a “high-performance” test for cervical cancer screening in lower resource settings, from SDGs perspective, to accelerate the achievement of second pillar elimination and the third SDGs target in 2030. Methods: This is a 7-year cross-sectional study. Subjects were recruited consecutively from several public and private health providers in Jakarta. VIA test was documented and consulted to the experts panel (TeleDoVIA). Negative VIA women underwent HPV-DNA testing using SPF10-DEIA-LiPA25 for PCR and electrophoresis. Results: A total of 1,397 negative VIA subjects were collected, consist of 52 HPV-DNA positive. False-negative of VIA was 3.7% (95% CI 0.027–0.047). Conclusion: VIA is a reliable screening method with a low false-negative rate. TeleDoVIA could be recommended as a reliable cervical cancer screening method in low resource settings such as Indonesia, which is in line with the third SDG: good health and well-being. Keywords: Southeast Asia < Asia; public health.